2020
DOI: 10.3233/jpd-202044
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Airway Invasion Using Screening Tools and Laryngeal Kinematics in People with Parkinson’s Disease: A Pilot Study

Abstract: Background: Dysphagia in Parkinson's disease (PD) is a common manifestation, particularly in advanced disease stages. However, the pathophysiology and time course of dysphagia progression remains unclear in non-advanced disease stages (e.g., Hoehn & Yahr stages I-III). Conflicting reports from investigations of the perception of dysphagia in people with PD further complicates our understanding of dysphagia in this population. Objective: The objectives of this research were to evaluate the ability of screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Neither the healthy control nor the PD group in our study was found to have any instances of incomplete LVC. This is in keeping with results from Dumican and Watts (2020) , who observed complete LVC in a cohort of individuals with nonadvanced PD. We did find increased frequencies of prolonged time-to-LVC across all consistencies in our PD cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Neither the healthy control nor the PD group in our study was found to have any instances of incomplete LVC. This is in keeping with results from Dumican and Watts (2020) , who observed complete LVC in a cohort of individuals with nonadvanced PD. We did find increased frequencies of prolonged time-to-LVC across all consistencies in our PD cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Results also indicated significant differences in time-to-LVC and LVCd.However, these measures as predictors for abnormal swallows were not significant in CVA patients. While time-to-LVC predicting penetration or aspiration supports our hypothesis and the current literature in PD[8][9][10] the lack of predictive ability of time-to-LVC in the CVA group was not expected, as time-to-LVC is often described as one of the major contributors to airway invasion in post-stroke dysphagia and most neurogenic etiologies of dysphagia[21, 22].The association of prolonged LVCd and airway invasion in PWPD has been postulated elsewhere[10] although the lack of association between LVCd and airway invasion in CVA agrees with the existing literature[53], in that LVCd by itself is not a strong predictor of airway invasion.From a clinical standpoint these findings provide important distinctions and suggest the need for increased awareness of how dysphagia manifests in different neurologically impaired populations. Though current literature suggests that time-to-LVC is one of the strongest predictors of airway invasion across neurogenic etiologies of dysphagia [12], it is possible that subgroups may be inflating the predictive power of generalized measures (i.e., timeto-LVC).…”
supporting
confidence: 87%
“…The laryngeal impairments which lead to aspiration in PWPD are not as well understood as those in cerebrovascular accident (CVA), which is considered one of the leading causes of dysphagia [7]. While recent evidence suggests that time-to-laryngeal vestibule closure (LVC) and airway responses to penetrated material are impacted by PD [8][9][10], greater evidence is needed to elucidate those physiological impairments for which treatment might have the greatest impact for swallowing safety and efficiency. This is particularly true as the prevalence of dysphagia in PD has been reported as similar to that of CVA [11], yet our understanding of laryngeal kinematics in CVA is substantially more robust compared to PD.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The laryngeal impairments which lead to aspiration in PWPD are not as well understood as those in cerebrovascular accident (CVA), which is considered one of the leading causes of dysphagia [7]. While recent evidence suggests that time-to-laryngeal vestibule closure (LVC) and airway responses to penetrated material are impacted by PD [8][9][10], greater evidence is needed to elucidate those physiological impairments for which treatment might have the greatest impact for swallowing safety and efficiency. This is particularly true as the prevalence of dysphagia in PD has been reported as similar to that of CVA [11], yet our understanding of laryngeal kinematics in CVA is substantially more robust compared to PD.…”
Section: Introductionmentioning
confidence: 99%